2013
DOI: 10.1182/blood-2012-07-442467
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal properties of red blood cells suggest a role in the pathophysiology of Gaucher disease

Abstract: Key Points• We provide evidence that red blood cells from patients suffering from Gaucher diseases exhibit morphologic and functional abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…The results obtained with this method in various diseases (diabetes, sepsis, Gaucher disease, etc) and situations (exercises) are usually in agreement with the results obtained with other methods, such as filtration or ektacytometry [6,18,[26][27][28]30], although filtration techniques may lack accuracy [3]. The mechanisms that lead to alterations in RBC deformability are slightly different between SS and SC disease [29], and SS patients are characterized by greater RBC alterations than SC patients [21,29].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results obtained with this method in various diseases (diabetes, sepsis, Gaucher disease, etc) and situations (exercises) are usually in agreement with the results obtained with other methods, such as filtration or ektacytometry [6,18,[26][27][28]30], although filtration techniques may lack accuracy [3]. The mechanisms that lead to alterations in RBC deformability are slightly different between SS and SC disease [29], and SS patients are characterized by greater RBC alterations than SC patients [21,29].…”
Section: Discussionsupporting
confidence: 79%
“…Exercise may increase or decrease RBC deformability by 5-12% from baseline values, [11,14,16]. Finally, a number of studies found a 5-10% RBC deformability difference between healthy populations and several several non-erythroid diseases characterized by hemorheological disorders, which play a role in the pathophysiological mechanisms [18,34]. Moreover, the significant negative linear regression shows a tendency for the bias to become negative with increasing RBC deformability.…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic pattern appears produced by a combination of reduced erythrocyte deformability and increased erythrocyte aggregation due to plasma protein changes [35]. There are lines of evidence that the red blood cells in other diseases too increase thixotropic properties of blood [36]. …”
Section: Discussionmentioning
confidence: 99%
“…9,10 We previously detected GCerase activity in normal erythroblasts but not in circulating RBCs. 11 High lipid levels have been frequently reported in the plasma and RBCs of GD patients, [22][23][24][25] which raises the possibility that the RBCs are overloaded with lipids due to the passive incorporation of GlcCer and/or that the erythroid progenitors are primarily affected. To evaluate the alterations in the erythroid progenitors, we performed in vitro experiments to study the erythroid differentiation from peripheral blood samples from GD type 1 patients.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] We have previously shown that the red blood cells (RBCs) of GD patients exhibit abnormal morphological, rheological and functional properties, and could be considered additional factors in the GD pathophysiology on the basis that they can trigger ischemic events. 11 Importantly, a study of a large cohort revealed that anemia was the only risk factor for avascular osteonecrosis, the most debilitating skeletal complication for GD type 1 patients. 12 Anemia affects 36% of GD patients.…”
Section: Introductionmentioning
confidence: 99%